Timber-Reinforced Concrete and Its Application in Portugal - Cristina Reis; Sandra Pereira; Naim Sedira; Anabela Paiva; Jorge Pinto (Buildings)
Traditional construction is an important skill. This paper intends to contribute to the literature on the topic of timber-reinforced concrete. First, some traditional Portuguese timber solutions are introduced. Second, some traditional Portuguese timber-reinforced concrete solutions are presented. Third, a sustainable concrete that uses waste from industrial timber aggregate is proposed. Some experimental work is also presented, along with some material properties. Fourth, an expedited experimental study of slender timber-reinforced concrete columns is introduced. Subsequently, some traditional Portuguese solutions for increasing the connection between timber and concrete are presented. The benefits of combining traditional techniques with modern materials for achieving greener and more resilient building solutions are emphasized.